THERMO-MECHANICAL MODIFICATION OF AMORPHOUS POLYESTER FIBRES: III. STRUCTURE INVESTIGATIONS USING WIDE ANGLE X-RAY SCATTERING: THERMO-MECHANICAL MODIFICATION OF AMORPHOUS POLYESTER FIBRES: III. STRUCTURE INVESTIGATIONS USING WIDE ANGLE X-RAY SCATTERING - Velev, Valentin; Popov, Anton; Kyurkchiev, Pencho; Veleva, Lyubomira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Amorphous poly (ethylene terephthalate) (PET) yarns were used as precursor specimens. The aim of the present experiment is to investigate the heat mechanically induced structural changes in the studied samples. The thermal deformation experiments were carried out on conditions of linear samples heating from room temperature up to 2000C while they were subjected to a well-defined constant strain force. Using of wide angle X-ray scattering (WAXS) and differential scanning calorimetry (DSC) methods ware investigated the structural rearrangements in the studied samples caused by the fibers drawing. Dependences between the parameters of the thermal deformation experiment and the running in the specimen’s structure development are established.